PENGARUH KEMUDAHAN, KEPERCAYAAN, DAN RISIKO TERHADAP MINAT BERTRANSAKSI MENGGUNAKAN FINANCIAL TECHNOLOGY (FINTECH) PERBANKAN SYARIAH PADA MASYARAKAT DI KABUPATEN KEDIRI - Luqmayanti, Fadillah; Solikah, Mar’atus; Widiawati, Hestin Sri (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine the effect of convenience, trust, and risk on the interest in transacting using Islamic banking fintech among people in Kediri Regency. The research method is causal associative quantitative. This research was conducted by distributing questionnaires via Google form to respondents. Meanwhile, in this study, the data sources used were primary data and secondary data. The data collection technique carried out by the author in this study is by using the questionnaire method (questionnaire) with the google form method. Data analysis techniques use the classic assumption test, multiple linear regression and hypothesis testing. The results of this study are (1) Ease has a positive and significant influence on the intention to transact using Islamic banking fintech (2) Trust has a positive and significant influence on the intention to transact using Islamic banking fintech (3) Risk has a positive and significant influence on the intention to transact using fintech Islamic banking (4) convenience, trust, and risk have a positive and significant effect on the interest in transactions using Islamic banking fintech. Many studies examine the factors that influence fintech, but it is still rare to find those that examine the factors that influence Islamic fintech and it is still very rare to examine the influence of convenience, trust, and risk on the interest in transacting using Islamic banking fintech in people in Kediri Regency.